Social participation of families with children with autism spectrum disorder in a science museum. (2nd July 2016) - Lussenhop, Alexander; Mesiti, Leigh Ann; Cohn, Ellen S.; Orsmond, Gael I.; Goss, Juli; Reich, Christine; Osipow, Allison; Pirri, Kayla; Lindgren-Streicher, Anna
ABSTRACT: This article describes a qualitative research study undertaken as a collaboration between museum and occupational therapy (OT) researchers to better understand museum experiences for families with a child or children impacted by autism spectrum disorder (ASD). Inclusion for visitors with ASD is an issue that museums are increasingly considering, and the social dimension of inclusion can be particularly relevant for this audience. The construct of social participation, used in OT, provides a promising avenue for museum professionals to think about inclusion. Social participation situates social and community experiences within the context of peoples' diverse motivations and the strategies they use to navigate environments. This study took these multiple factors into account when observing families' museum visits—including analysis of their motivations for visiting, environmental features that influenced their visit, family strategies used before and during the visit, and the families' definitions of a successful visit. Learning more about these factors that are associated with social participation can inform future efforts to improve museum inclusion for families with children with ASD.